The helpers' stress: Effectiveness of a web-based intervention for professionals working with trauma survivors in reducing job burnout and improving work engagement - Anna Rogala; Ewelina Smoktunowicz; Katarzyna Żukowska; Martyna Kowalska; Roman Cieślak (Nofer Institute of Occupational Medicine, 2016)
Background: The study aimed at evaluating effectiveness of the web-based intervention, "The Helpers' Stress," in reducing job burnout and enhancing work engagement among professionals working with trauma survivors. Material and Methods: Participants were randomly allocated to 1 of the 3 intervention modules: 1 - the self-efficacy enhancement (N = 87), 2 - the social support enhancement (N = 85), or to 3 - the educational module (comparison group, N = 81). Participants completed the online questionnaires before the intervention (T1), immediately after (T2), and 4 weeks after the intervention (T3). Results: Due to high drop-out rate at T2 and T3 in social support enhancement module, we excluded from analysis participants assigned to this condition. Participants assigned to the self-efficacy enhancement module presented higher levels of self-efficacy (at T2 and T3), compared to those assigned to the educational module. Job burnout decreased significantly between T1 and T2, and between T2 and T3, and work engagement increased significantly between T1 and T2, and between T1 and T3, among participants assigned to both modules mentioned above. Self-efficacy (T2) mediated the relationship between the group assignment (educational module vs. self-efficacy enhancement module) and respectively job burnout (T3) or work engagement (T3). Conclusions: The results of our study highlight the role of self-efficacy in reducing job burnout and increasing work engagement. Med Pr 2016;67(2):223-237